Examining the impact of industry 4.0 on academic libraries - Chigwada, Josiline Phiri, 1984-; Nwaohiri, Ngozi Maria, 1972- (Bingley, UK : Emerald Publishing, 2021)
As the rapid acceleration of industry 4.0 catapults a number of changes within the space of library services and operations into effect, it is more important than ever to understand the impact of technological revolutions on the academic library. This edited collection showcases the emerging issues brought by the 4th industrial revolution, and the effects on how libraries function, manage processes and continue to deliver products and services on a day to day basis--back cover.
Includes bibliographical references and index.
Keywords: Academic libraries -- Effect of technological innovations on; Industry 4.0.; Industry 4.0.; Academic libraries -- Effect of technological innovations on